Perception and Cognition of Music - Deliège, Irène; Sloboda, John A. (East Sussex Psychology Press, 1997)
This text comprises of reviews of work relating to music and mind. It presents a range of approaches from the psychological through the computational, to the musicological. The reviews were selected from papers submitted at the Third International Conference on Music Perception and Cognition Liege 1994 to illustrate the wide range of perspectives now being adopted in studying how humans make and respond to music. The book is divided ino five sections. The first part illustrates the role of analysis and ethnomusicology in understanding cultural determinants of musical behaviour. The second part charts what is known about aquisition of musical competence, from pre-birth through to the expert performer. The evidence accumulated about specific areas of the brain which control musical thinking and behaviour is examined in Part Three. The fourth part examines how neurological, behavioural and artificial intelligence approaches are converging to shed light on processes in auditory perception. Finally, Part Five highlights the important developments in how we conceptualize the way in which musical structures are represented in the mind.
Keywords: Music psychology; Music philosophy and esthetics